Perceptions of a police-initiated diversion program: a qualitative study. Issue 1 (2nd January 2023) - Kidd, Taylor; Magidson, Mark
ABSTRACT: Police-initiated diversion practices allow officers to divert youth away from the justice system. This qualitative study addresses one such Southern California program to understand the subjective experiences of youth and parents through in-depth interviews. Thirty-eight respondents, 19 youth and 19 parents, were interviewed for this study. Results demonstrate how an increase in positive interactions with police officers and diversion program staff can influence how youth comply with the law and legal institutions. Interviews emphasized youths' complex attitudes toward police and the law, highlighting the importance for police and diversion programs to engage in transparent practices to facilitate a greater understanding of diversion and reduce potentially traumatic feelings from initial police contact.